Characterization of EST3: a metagenome-derived esterase with suitable properties for biotechnological applications - Maester, Thaís Carvalho [UNESP]; Pereira, Mariana Rangel [UNESP]; Machado Sierra, E. G. [UNESP]; Balan, Andrea; de Macedo Lemos, Eliana Gertrudes [UNESP] (Springer Nature, 2016)
Metagenomic libraries from diverse environments have been extensive sources of many lipases and esterases; nevertheless, most of these enzymes remain biochemically uncharacterized. We previously built a metagenomic fosmid library from a microbial consortium specialized for diesel oil degradation and tested it for lipolytic activity. In the present study, we identified the PL14.H10 clone that was subcloned and sequenced, which enabled the identification of the EST3 protein. This enzyme exhibited 74 % amino acid identity with the uncharacterized alpha/beta hydrolase from Parvibaculum lavamentivorans [GenBank: WP012110575.1] and was classified into lipolytic enzyme family IV. Biochemical characterization revealed that EST3 presents high activity in a wide range of temperature with highest activity from 41 to 45 °C. Also, this thermostable esterase acts from mild acidic to alkaline conditions with an optimum pH of 6.0. The enzyme exhibited activity against p-nitrophenyl esters of different chain lengths and highest catalytic efficiency against p-nitrophenyl caprylate. The activity of the protein was increased in the presence of 0.5 mM of Mn+2, Li+, EDTA, and 1 % of CTAB and exhibited half of the activity in the presence of 10 % methanol and ethanol. Moreover, the homology model of EST3 was built and compared to other esterases, revealing a substrate channel that should fit a wide range of substrates. Taken together, the data presented in this work reveal the unique and interesting characteristics of EST3 that might be explored for further use in biotechnological applications.
Keywords: Esterase; Family IV; Lipase; Microbial consortium; pNP esters